2021
DOI: 10.1371/journal.pone.0253874
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surgical and N95 face masks on speech perception and listening effort in noise

Abstract: Daily-life conversation relies on speech perception in quiet and noise. Because of the COVID-19 pandemic, face masks have become mandatory in many situations. Acoustic attenuation of sound pressure by the mask tissue reduces speech perception ability, especially in noisy situations. Masks also can impede the process of speech comprehension by concealing the movements of the mouth, interfering with lip reading. In this prospective observational, cross-sectional study including 17 participants with normal hearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 27 publications
1
45
0
4
Order By: Relevance
“…The effects of face masks on speech comprehension have been investigated in various studies on a behavioural level (Brown et al, 2021;Giovanelli et al, 2021;Rahne et al, 2021;Toscano & Toscano, 2021;Yi et al, 2021). Despite the overall agreement of adverse effects of face masks on speech comprehension, it has been unclear which features of speech processing are specifically affected.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of face masks on speech comprehension have been investigated in various studies on a behavioural level (Brown et al, 2021;Giovanelli et al, 2021;Rahne et al, 2021;Toscano & Toscano, 2021;Yi et al, 2021). Despite the overall agreement of adverse effects of face masks on speech comprehension, it has been unclear which features of speech processing are specifically affected.…”
Section: Discussionmentioning
confidence: 99%
“…Such degradation can be mild ~2d B with a surgical mask and an FFP2 mask (Bottalico et al, 2020 ; Cruz et al, 2022 ) to more intense ~20 dB with transparent masks (Atcherson et al, 2020 ). Face masks, again depending on the material, affect other aspects of the acoustic signal, such as power distribution, spectral tilt, and timing, which are particularly affected by the FFP2 face mask (Rahne et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The speech is produced by the vocal folds vibration induced air vibration when vocal folds come close as the air passing through during the exhalation of air from the lung [39]. Although a few research also suggest medical masks have no negative effect on speech understanding [40], more recent investigations have further demonstrated that both standard surgical masks and N95/KN95 respirators have an influence on the acoustic characteristics of voice [41-44], attenuating the mean spectral level by 2.0–5.2 dB in the high-frequency region from 1 to 8 kHz while not significantly affecting the low-frequency range from 0 to 1 kHz [41]. Additionally, the masks with higher barrier level have been proved to have greater attenuation of high-frequency components during the transmission of sound [41, 42], and masks impact more on human speech recognition in a higher level of background noise [45].…”
Section: Introductionmentioning
confidence: 99%
“…The speech is produced by the vocal folds vibration induced air vibration when vocal folds come close as the air passing through during the exhalation of air from the lung [39]. Although a few research also suggest medical masks have no negative effect on speech understanding [40], more recent investigations have further demonstrated that both standard surgical masks and N95/KN95 respirators have an influence on the acoustic characteristics of voice [41][42][43][44],…”
Section: Introductionmentioning
confidence: 99%